ROLE OF CSR TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN INDIA: OPPORTUNITIES AND CHALLENGES - Dr. Sunita Pachar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this study we explore the relationship between corporate social responsibility (CSR) and Sustainable Development Goals (SDGs). Indian Corporate sector can contribute in Sustainability Development Goals through its CSR practices .Corporate Social Responsibility dimensions like economical , Social or Environmental all can be interlinked with SDG and it can be helpful to tackle many challenges which India is facing .It can be seen that SDG and CSR both have same objective or purpose as Development of India .Corporate should integrate SDG into the core of their functioning strategies then they easily can contribute in CSR and SDG .This study main focus is to understand that how Indian corporate is contributing in SDG through their CSR efforts and by making better planning they can contribute more .This study offers some recommendations also to overcome the challenges which organizations are facing while implementing CSR Practices .